Tinker, Tailor, Soldier - Awry? Assignment Problem in Disinflation Endeavours - Malovic, Marko G (Poslovna ekonomija, 2024)
Abstract: Overcoming macroeconomic hurdles as a trade assumes that branches of government are almost continuously charged with various assignments, or particular tasks attached to a finite set of resources and talents owned by organisational subunits with decision rights in corrective policy-making. Even though open-economy cases of disinflation programmes reminded us quite a while ago that one task need not be assigned to one single resource exclusively, the overwhelming belief in mainstream macro to this day is that monetary policy remains chiefly responsible for both causing and stopping harmful inflation spirals. This paper, however, follows a novel wave of literature which doubly questions the aforementioned notion. It appears that the usual suspects for recent rise of inflation worldwide are found not guilty, hence we stand by the rare few who advocate that inflation in a modern non- Ricardian setting, when it finally spiraled out of control, represents but a legitimate and inevitable consequence of irresponsible fiscal policies and unsustainably high public (and private) debts. Moreover, due to familiar if reversed Fisherian effect, intermediated monetary restriction via interest rate hikes turns out to be unsafe, rather controversial reaction of central banks when it comes to reasonably swift and reliable preference for an outcome of such disinflation endeavours.